Strategies to Reduce Left Anterior Descending Artery and Left Ventricle Organ Doses in Radiotherapy Planning for Left-Sided Breast Cancer - Umut Diremsizoglu; Nezihan Topal; Aykut Oguz Konuk; Ibrahim Halil Suyusal; Dogacan Genc; Onur Ari; Hasan Furkan Cevik; Aysegul Ucuncu Kefeli; Maksut Gorkem Aksu; Emine Binnaz Sarper (Reviews in Cardiovascular Medicine)
Background: One of the most significant long-term toxicities of breast cancer radiotherapy is major adverse cardiac events (MACE). In current radiotherapy practice, the mean heart dose is the most commonly used parameter. The aim of our study was to reduce the doses of organs at risk (OAR) in the left anterior descending artery (LAD) and left ventricle (LV) by including the LAD and LV in planning radiotherapy while maintaining adequate dose coverage for patients with left-sided breast cancer. Methods: We retrospectively analyzed left-sided breast cancer cases treated at the Kocaeli University Faculty of Medicine. Only patients with local and locally advanced breast cancer were included in the analysis. A total of 77 patients who were treated between 2020 and 2024 were included. The doses to the LAD and LV were added to the optimization algorithms. Two volumetric modulated arc therapy (VMAT) plans were created for each patient. A total of 154 plans were made, including standard and LAD and LV sparing plans. Results: There was no statistically significant difference in all VMAT plans regarding planning target volume (PTV) D2, D50, and D98 (dose receiving volume of PTV 2%, 50%, and 98%) (p > 0.05). However, a significant decrease was observed in heart V5 (the percentage of the heart receiving at least 5 gray (Gy)) and mean heart dose. A decrease in the mean heart dose was observed in the standard plan compared with the LAD and LV sparing plan (p < 0.001). Similarly, the heart V5 value decreased significantly (p < 0.001). Additionally, significant reductions were measured in all LAD and LV parameters after re-optimization. Conclusions: We achieved significant reductions in all heart, LAD, and LV parameters without making any changes to the planned treatment volume coverage by adding LAD and LV OARs to the optimization algorithms. The potential risk of MACE can be significantly reduced by implementing this strategy.